UNDERSTANDING THE FACTORS OF FINANCIAL INNOVATION IN INDUSTRIAL REVOLUTION 4.0 ERA - Sinaga, Hizkia Edwar; Windijarto, Windijarto; Halawa, Forman; Mbate, Clarasiska Anasthasia (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2023)
Financial innovation is a way of creating new financial products, services or processes effectively and efficiently. This study aims to examine the factors of financial innovation termed as the antecedents and consequences of implementing financial innovation at both micro and macroeconomic levels and to assist future researchers in determining research topics related to financial innovation. This research applies a Systematic Literature Review (SLR) method using 58 relevant articles from the Scopus database, which were examined and became the study results. This study discovers 14 antecedents and 53 consequences to financial innovation since the development of the Industrial Revolution 4.0 era. Even though there are still limitations within this article, this research does provide recommendations for future studies related to financial innovation in the Society 5.0 era.